O konieczności dalszego rozwoju tzw. wychowania literackiego = On the necessity of further evolution of literary education - Plch, Jaromir (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author ponders on the scientific conception of literary education through the art of words and comes to the conclusion that researches up to the present too one-sided defined the relation between perceiving subjects (teacher and student) and the artistic work in the process of educational schooling. The scholar proposes the separation of two kinds of interaction (a didactic and an aesthetic) and calls for special attention to the aesthetic interaction, in which the artistic work shows itself as an unique and polyfunctional integrity.
Keywords: wychowanie literackie